2017
DOI: 10.1136/bmjopen-2016-011637
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness and safety of erythropoiesis-stimulating agents (biosimilars vs originators) in clinical practice: a population-based cohort study in Italy

Abstract: ObjectivesTo evaluate the benefit/risk profile of epoetin α biosimilar with the erythropoiesis-stimulating agents (ESAs) originators when administered to naïve patients from clinical practice.DesignPopulation-based observational cohort study.SettingAll residents in the Lazio Region, Italy, with chronic kidney disease (CKD) or cancer retrieved from the Electronic Therapeutic Plan (ETP) Register for ESA between 2012 and 2014.ParticipantsOverall, 13 470 incident ESA users were available for the analysis, 8161 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 26 publications
1
13
0
1
Order By: Relevance
“…Data from the ORHEO (place of biOsimilaRs in the therapeutic management of anemia secondary to chemotherapy in HaEmatology and Oncology) observational study ( n = 2333) in France, conducted primarily in patients using SB309, indicate a post-marketing safety profile consistent with the reference epoetin alfa [ 30 , 31 ]. More recently, a population-based observational cohort study of more than 13,000 patients reported no difference in safety outcomes between treatment with biosimilar epoetins, reference epoetin alfa, and other ESAs [ 32 ]. Thus, for those initially concerned about the safety of epoetin biosimilars, reassurance is provided by data now accumulated, which demonstrate that there have been no specific safety signals after 10 years of clinical usage in Europe.…”
Section: Initial Concerns About the Introduction Of Biosimilar Epoetimentioning
confidence: 99%
“…Data from the ORHEO (place of biOsimilaRs in the therapeutic management of anemia secondary to chemotherapy in HaEmatology and Oncology) observational study ( n = 2333) in France, conducted primarily in patients using SB309, indicate a post-marketing safety profile consistent with the reference epoetin alfa [ 30 , 31 ]. More recently, a population-based observational cohort study of more than 13,000 patients reported no difference in safety outcomes between treatment with biosimilar epoetins, reference epoetin alfa, and other ESAs [ 32 ]. Thus, for those initially concerned about the safety of epoetin biosimilars, reassurance is provided by data now accumulated, which demonstrate that there have been no specific safety signals after 10 years of clinical usage in Europe.…”
Section: Initial Concerns About the Introduction Of Biosimilar Epoetimentioning
confidence: 99%
“…The only RCT in patients with cancer 30 had a high likelihood of bias based on inadequate sample size, lack of an intent-to-treat analysis, and industry funding and authorship. The quality of the four included cohort studies of biosimilars [31][32][33][34] in patients with cancer was not formally assessed.…”
Section: Resultsmentioning
confidence: 99%
“…The systematic review of biosimilar ESAs included two metaanalyses 27,28 and one RCT 29 in patients with CKD, and one RCT 30 and three cohort studies [31][32][33] in patients with cancer. In a 2017 meta-analysis of RCTs in CKD, Amato et al 27 reported that efficacy and safety outcomes did not differ significantly between patients treated with epoetin alfa originator or biosimilar but described the quality of evidence as low to very low.…”
Section: Recommendationmentioning
confidence: 99%
See 1 more Smart Citation
“…Guidelines also advise compensating any hematinic deficiencies with erythropoiesis-stimulating agents, iron, folic acid and vitamin B12 [3]. In our case, we used epoetin alfa intravenously as oppose to subcutaneous route, as it allows faster patient response and greater flexibility in terms of dosing [4].…”
Section: Discussionmentioning
confidence: 99%